Level of education as moderator of age-job satisfaction relationship - Parmač, Maja (2007)
Over the last sixty years, personal and situational predictors of job satisfaction have been examined extensively. Among personal characteristics that can influence job satisfaction, age was most frequently studied. Generally, the studies examining relationship between the two variables indicate small positive correlation between age and job satisfaction. However, the nature of this relationship is probably a function of the occupational group examined (Oshagbemi, 2003). Considering, that one of the most salient characteristic of employees is their level of education, the aim of this study is to examine whether the age change in job satisfaction is different for employees with different educational levels. Data were collected on a large sample of employees (N=2593) during 13-year period through a self-report questionnaire measuring general job satisfaction and satisfaction with specific job aspects. The results showed that the age related change in general job satisfaction was the same for employees belonging to different educational groups. However, significant interaction between age and level of education was found for satisfaction with the job aspects related to payment (satisfaction with amount of income and pay fairness). It seems that for employees of different educational levels patterns of convergence between payment aspirations and opportunities offered by job depend on age.